Societal Transformation in the Islamic World: Rethinking Social Interaction During the Arab Spring - Alvin Dermawan Sukardi; Aris Munandar (TSAQAFAH, 2026)
This study re-evaluates the foundational drivers of the Arab Spring, challenging the conventional narrative that the uprisings were primarily fueled by political ideology, religious motivations, or allegiances to specific geopolitical blocs. Instead, it examines how the movement underscored the efficacy of grassroots "people power" in dismantling long-standing authoritarian regimes and establishing new social structures across the Islamic world. Adopting a qualitative methodology grounded in extensive library research and an ethnographic research approach, the study analyzes the shifting paradigms of social interaction, cultural transformations, and the lived experiences of the societies involved. The findings reveal that the trajectory of the Arab Spring was inextricably linked to the strategic utilization of digital and social media platforms, most notably Facebook and YouTube. Youth-led demographics leveraged these tools to transform traditional, localized forms of protest into decentralized, digital-based movements capable of rapid mass mobilization and information dissemination. Furthermore, the study highlights how the post-Arab Spring landscape catalyzed a significant shift in regional geopolitics, prominently marked by the assertive role of Saudi Arabia. As a dominant regional power, Saudi Arabia’s subsequent foreign policies have been systematically calibrated to protect domestic stability, counter the proliferation of political Islamist groups, and assert influence over the fractured Middle Eastern political dynamic. Ultimately, by shifting the analytical lens from macro-political treaties to micro-societal interactions and digital networks, this research offers a fresh perspective on how digital spaces redefine collective action and geopolitical recalibration in the modern Islamic world.